2020
DOI: 10.1101/2020.06.04.134288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural divergence and convergence for attention to and detection of interoceptive and somatosensory stimuli

Abstract: 1Body awareness is constructed by signals originating from within and outside the body. How do 2 these apparently divergent signals converge? We developed a signal detection task to study the 3 neural convergence and divergence of interoceptive and somatosensory signals. Participants focused 4 on either cardiac or tactile events and reported their presence or absence. Beyond some evidence of 5 divergence, we observed a robust overlap in the pattern of activation evoked across both conditions 6 in frontal areas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 122 publications
(111 reference statements)
1
2
1
Order By: Relevance
“…Another possible explanation for the difference may be due to the fact that participants in the former study were counting heartbeats with their eyes closed and time intervals used in the task were shorter (18/20/22 seconds). The observed correlation between HCT and VCT performance also corresponds with another study, comparing heartbeat perception with somatosensory stimuli (Herman et al, 2020). Although direct comparison is not possible due to the modification of the heartbeat counting task used in that study, our findings support the idea of overlapping mechanisms between interoception and exteroception.…”
Section: Confirmatory Analysessupporting
confidence: 88%
See 1 more Smart Citation
“…Another possible explanation for the difference may be due to the fact that participants in the former study were counting heartbeats with their eyes closed and time intervals used in the task were shorter (18/20/22 seconds). The observed correlation between HCT and VCT performance also corresponds with another study, comparing heartbeat perception with somatosensory stimuli (Herman et al, 2020). Although direct comparison is not possible due to the modification of the heartbeat counting task used in that study, our findings support the idea of overlapping mechanisms between interoception and exteroception.…”
Section: Confirmatory Analysessupporting
confidence: 88%
“…This prompts a second question about the HCT, namely whether performance levels in it reflect interoceptive accuracy per se or if they instead also reflect individual propensities for the reporting of uncertain stimuli in general. Evidence that this may be the case comes from prior work demonstrating correlations between reporting behaviour in the HCT and in matched somatosensory and auditory tasks (Herman et al, 2020;Larsson et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…In sighted individuals, performance on tasks involving cardiac interoception has been consistently linked to activation of regions related to the processing of visceral interoceptive signals, such as the insular cortex (Cameron & Minoshima, 2002;Critchley et al, 2004;Herman et al, 2021;Stern et al, 2017;Zaki et al, 2012) and the anterior cingulate cortex (Caseras et al, 2013;García-Cordero et al, 2016;Khalsa et al, 2009;Kleckner et al, 2017). However, in our study, no associations were observed between cardiac interoception and cortical thickness in these regions, for both blind and sighted participants.…”
Section: Discussioncontrasting
confidence: 57%
“…By contrast,Herman, Palmer, Azevedo, & Tsakiris (2021) have demonstrated that attention to and detection of interoceptive signals can lead to increased activations of the occipital cortex, potentially pointing to a functional role of the occipital cortex during interoceptive tasks. The exact relationship between visceral signal processing and the occipital cortex in sighted individuals remains to be clarified (see Azzalini, Rebollo, & Tallon-Baudry, 2019).…”
mentioning
confidence: 82%